Implementasi Pengorganisasian Pembelajaran Pendidikan Agama Islam Dalam Memotivasi Belajar Peserta Didik di SMP Negeri 5 Kota Tangerang - Kurniati, Ety (AL-WIJDÃN Journal of Islamic Education Studies, 2022)
This study discusses the organization of Islamic religious education learning in motivating students' learning at SMP Negeri 5 Tangerang City. The author uses descriptive qualitative research methods, the author describes the data collected through observation, interviews and documentation then analyzed through three components, namely data reduction, data presentation, and data verification. This article shows that organizing learning in PAI subjects can motivate students' learning in the learning process. The obstacles and solutions faced in organizing PAI learning in motivating students' learning are incomplete facilities and infrastructure, cooperation between teachers and students' parents, and uneven student interest in learning. While the solution that was carried out by both the school and the PAI teacher was that the school tried as much as possible to complete the facilities and infrastructure in maximizing the learning process. Improving the competence of teachers through training activities held by the relevant agencies in maximizing their competence as educators. The author recommends that schools should strive to meet all facilities and infrastructure to support the quality of learning, teachers and schools need to increase cooperation with parents of students. This article will describe how organizing is meant to work well.                                                                                                      Keywords: Organizing Learning, Learning Motivation